Visible-light driven heterojunction photocatalysts for water splitting – a critical review. Issue 3 (22nd January 2015) - Moniz, Savio J. A.; Shevlin, Stephen A.; Martin, David James; Guo, Zheng-Xiao; Tang, Junwang
Abstract : We summarise current state-of-the-art efficient visible-light driven heterojunction water splitting photo(electro)catalysts and describe how theoretical modelling of electronic structures at interfaces can explain their functionality. Abstract : Solar driven catalysis on semiconductors to produce clean chemical fuels, such as hydrogen, is widely considered as a promising route to mitigate environmental issues caused by the combustion of fossil fuels and to meet increasing worldwide demands for energy. The major limiting factors affecting the efficiency of solar fuel synthesis include; (i) light absorption, (ii) charge separation and transport and (iii) surface chemical reaction; therefore substantial efforts have been put into solving these problems. In particular, the loading of co-catalysts or secondary semiconductors that can act as either electron or hole acceptors for improved charge separation is a promising strategy, leading to the adaptation of a junction architecture. Research related to semiconductor junction photocatalysts has developed very rapidly and there are a few comprehensive reviews in which the strategy is discussed (A. Kudo and Y. Miseki, Chemical Society Reviews, 2009, 38, 253–278, K. Li, D. Martin, and J. Tang, Chinese Journal of Catalysis, 2011, 32, 879–890, R. Marschall, Advanced Functional Materials, 2014, 24, 2421–2440). This critical review seeks to give an overview of the concept of heterojunction construction and more importantly, the current state-of-the art for the efficient, visible-light driven junction water splitting photo(electro)catalysts reported over the past ten years. For water splitting, these include BiVO4, Fe2 O3, Cu2 O and C3 N4, which have attracted increasing attention. Experimental observations of the proposed charge transfer mechanism across the semiconductor/semiconductor/metal junctions and the resultant activity enhancement are discussed. In parallel, recent successes in the theoretical modelling of semiconductor electronic structures at interfaces and how these explain the functionality of the junction structures is highlighted.